2010
DOI: 10.3109/17453674.2010.533933
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and radiological outcomes of hip resurfacing versus total hip arthroplasty: a meta-analysis and systematic review

Abstract: Background and purposeHip resurfacing (HRS) procedures have gained increasing popularity for younger, higher-demand patients with degenerative hip pathologies. However, with concerns regarding revision rates and possible adverse metal hypersensitivity reactions with metal-on-metal articulations, some authors have questioned the hypothesized superiority of hip resurfacing over total hip arthroplasty (THA). In this meta-analysis, we compared the clinical and radiological outcomes and complication rates of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 102 publications
2
29
0
Order By: Relevance
“…At a minimum 1-year followup, Rama et al [6] found an increased incidence and severity of ectopic bone formation in SRA compared to conventional THA, hypothesizing the need to routinely adopt preventive measures after hip resurfacing procedures. Similarly, in a recent meta-analysis study, a significantly higher presence of HO was detected in resurfaced hips [7]. …”
Section: Introductionmentioning
confidence: 73%
“…At a minimum 1-year followup, Rama et al [6] found an increased incidence and severity of ectopic bone formation in SRA compared to conventional THA, hypothesizing the need to routinely adopt preventive measures after hip resurfacing procedures. Similarly, in a recent meta-analysis study, a significantly higher presence of HO was detected in resurfaced hips [7]. …”
Section: Introductionmentioning
confidence: 73%
“…6 A further systematic review comparing hip resurfacing with THR demonstrated that while resurfacing may give a better functional outcome, THR has better survivorship. 7 It is important to note that, as with survivorship, using PROMs alone can cause problems. Logistically, questionnaires are more labour intensive and expensive to collect than survivorship data.…”
mentioning
confidence: 99%
“…Reported disadvantages include increased risk of femoral neck fracture, more bone loss on the acetabular side, a more difficult operation requiring larger incisions, and increased risk of systemic exposure to metal ions resulting from wear of the metal-on-metal bearing surface. [44][45][46][47][48][49] Hip resurfacing is predominantly considered for the young active patient with end-stage osteoarthritis. 47 Early and mid-term follow-up generally has shown comparable results to those of standard replacement.…”
Section: Obesitymentioning
confidence: 99%